Tetrahedrite Nanocomposites for High Performance Thermoelectrics - Rodrigo Coelho; Duarte Moço; Ana I. de Sá; Paulo P. da Luz; Filipe Neves; Maria de Fátima Cerqueira; Elsa B. Lopes; Francisco P. Brito; Panagiotis Mangelis; Theodora Kyratsi; António P. Gonçalves (Nanomaterials)
Thermoelectric (TE) materials offer a promising solution to reduce green gas emissions, decrease energy consumption, and improve energy management due to their ability to directly convert heat into electricity and vice versa. Despite their potential, integrating new TE materials into bulk TE devices remains a challenge. To change this paradigm, the preparation of highly efficient tetrahedrite nanocomposites is proposed. Tetrahedrites were first prepared by solid state reaction, followed by the addition of MoS2 nanoparticles (NPs) and hot-pressing at 848 K with 56 MPa for a duration of 90 min to obtain nanocomposites. The materials were characterized by XRD, SEM-EDS, and Raman spectroscopy to evaluate the composites’ matrix and NP distribution. To complement the results, lattice thermal conductivity and the weighted mobility were evaluated. The NPs’ addition to the tetrahedrites resulted in an increase of 36% of the maximum figure of merit (<semantics>zT</semantics>) comparatively with the base material. This increase is explained by the reduction of the material’s lattice thermal conductivity while maintaining its mobility. Such results highlight the potential of nanocomposites to contribute to the development of a new generation of TE devices based on more affordable and efficient materials.